Humanization in intensive care units nurse participation (Research, Society and Development, 2022)
Humanized nursing care in the ICU will only occur if there is an existential involvement of caregivers with the sick and family, where the experience is lived and shared, enabling care that breaks with the predominant care model, whose main objective is healing. The present study aims to describe the role of nurses in the context of humanization in ICUs. This is a descriptive exploratory study with a qualitative approach, the inclusion criterion used in the study was based on scientific articles focused on the topic addressed, data collection will be made using the keywords used in the technique of content analysis proposed by Bardin. From the theoretical survey carried out in this work, it was possible to understand, within the various approaches presented on the subject, the relevance of nurses' participation when it is intended to humanize Intensive Care Units (ICUs). For all these factors presented throughout the study, it is valid to inform that it is increasingly necessary to deepen studies in this area, involving the multidisciplinary team and making clear the principles, methods and guidelines to be followed in order to seek a more humanized practice.